Synthesis and structure−activity relationships of teixobactin. Issue 1 (2nd December 2019) - Karas, John A.; Chen, Fan; Schneider‐Futschik, Elena K.; Kang, Zhisen; Hussein, Maytham; Swarbrick, James; Hoyer, Daniel; Giltrap, Andrew M.; Payne, Richard J.; Li, Jian; Velkov, Tony
Abstract: The discovery of antibiotics has led to the effective treatment of bacterial infections that were otherwise fatal and has had a transformative effect on modern medicine. Teixobactin is an unusual depsipeptide natural product that was recently discovered from a previously unculturable soil bacterium and found to possess potent antibacterial activity against several Gram positive pathogens, including methicillin‐resistant Staphylococcus aureus and vancomycin‐resistant Enterococci . One of the key features of teixobactin as an antibiotic lead is that resistance could not be generated in a laboratory setting. This is proposed to be a result of a mechanism of action that involves binding to essential cell wall synthesis building blocks, lipid II and lipid III. Since the initial isolation report in 2015, significant efforts have been made to understand its unique mechanism of action, develop efficient synthetic routes for its production, and thus enable the generation of analogues for structure−activity relationship studies and optimization of its pharmacological properties. Our review provides a comprehensive treatise on the progress in understanding teixobactin chemistry, structure−activity relationships, and mechanisms of antibacterial activity. Teixobactin represents an exciting starting point for the development of new antibiotics that can be used to combat multidrug‐resistant bacterial ("superbug") infections. Abstract : Our review provides a comprehensive treatise on the progress in understanding teixobactin chemistry, structure−activity relationships, and mechanisms of antibacterial activity. Teixobactin represents an exciting starting point for the development of new antibiotics that can be used to combat multidrug‐resistant bacterial ("superbug") infections.